Pelatihan Pembuatan Sabun Cuci Piring Organik Sebagai Upaya Menumbuhkan Jiwa Wirausaha Siswa SMKS Sunan Drajat Jember - Danu Indra Wardhana; Anisa Nurina Aulia; Andika Putra Setiawan; Fina Syafia; Firlana Rosa (Indonesian Journal Publisher, 2023)
Vocational High Schools should be able to produce entrepreneurs who can create businesses independently for their lives. But in reality, there are some SMK alumni who haven't got a job after graduating from school. This can be avoided from the beginning of their education an interest in entrepreneurship is cultivated so that when they graduate, they can choose to become entrepreneurs. On the other hand, every human activity produces waste (garbage). Excessive waste production can cause problems for the environment. In addition to having an unpleasant smell, flies often infest garbage and can cause disease outbreaks, some of the waste that is abundant in the environment is fruit peel waste. The use of fruit peels in dosage forms is still little done, and product preparations in circulation are still very minimal to be found, even though the use of fruit peels is fairly easy to find, economical and practical. Based on the above conditions, it is necessary to have activities to increase the interest in entrepreneurship for SMK students in harmony with sustainable waste management. One of the alternative activities is Entrepreneurship Training by making organic soap from fruit peel waste. The methods used are identifying partner needs, designing activities, mentoring, implementing, and evaluating sustainability. The result of this training is that students practice directly making organic dish soap, it is hoped that the data will make alternative business products.